2021
DOI: 10.2217/nnm-2021-0255
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for Cancer: Effects of Iron Oxide Nanoparticles on Polarization of Tumor-Associated Macrophages

Abstract: Cancer immunotherapy is the most promising trend in oncology, focusing on helping or activating the patient's immune system to identify and fight against cancer. In the last decade, interest in metabolic reprogramming of tumor-associated macrophages from M2-like phenotype (promoting tumor progression) to M1-like phenotypes (suppressing tumor growth) as a therapeutic strategy against cancer has increased considerably. Iron metabolism has been standing out as a target for the reprogramming of tumor-associated ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 98 publications
0
34
0
Order By: Relevance
“…Liposome-Encapsulated CpG (cytosine-phosphorothioate-guanine) Oligodeoxynucleotides (CpG-ODNs) exhibit potent immunostimulating activity by binding with Toll-like receptor 9 (TLR9) expressed on DC cells and activating NK cells, NKT cells and enhance expression of the early activation molecule CD69 on conventional T cells ( 156 ). Iron oxide nanoparticles also can simultaneously promote the reprogramming of tumor-associated macrophages to a pro-inflammatory profile and effectively deliver the ovalbumin antigen (OVA) to dendritic cells and activate both CD4+ and CD8+ antigen-specific T effector cells is achieved for powerful antitumor effects in female C57/BL6 mice injected with EG7-OVA cells (mouse lymphoma cell line) ( 157 , 158 ).…”
Section: Immunotherapy Based On Nanotechnologymentioning
confidence: 99%
“…Liposome-Encapsulated CpG (cytosine-phosphorothioate-guanine) Oligodeoxynucleotides (CpG-ODNs) exhibit potent immunostimulating activity by binding with Toll-like receptor 9 (TLR9) expressed on DC cells and activating NK cells, NKT cells and enhance expression of the early activation molecule CD69 on conventional T cells ( 156 ). Iron oxide nanoparticles also can simultaneously promote the reprogramming of tumor-associated macrophages to a pro-inflammatory profile and effectively deliver the ovalbumin antigen (OVA) to dendritic cells and activate both CD4+ and CD8+ antigen-specific T effector cells is achieved for powerful antitumor effects in female C57/BL6 mice injected with EG7-OVA cells (mouse lymphoma cell line) ( 157 , 158 ).…”
Section: Immunotherapy Based On Nanotechnologymentioning
confidence: 99%
“…Furthermore, we sought to broaden our understanding of the mechanisms of iron oxide-based macrophage repolarization and tumor inhibition. Fenton reaction has been considered as the innate reason for macrophage conversion and ROS is one significant production mediated the process [ 16 , 46 ]. Thus, we examined the ROS releasing from macrophages and found that HA-man@Fe 3 O 4 induced the highest ROS amount in all iron oxide-treated groups, corresponding to the strongest skewing effect shown in flow cytometry and ELISA assay ( Figure 3 A–H).…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytosis of NPs can influence TAM polarization because these particles are recognized as foreign bodies. IONPs demonstrated a potent effect on TAM polarization due to iron transporter-related protein expression [ 311 , 312 , 313 ]. Kodali et al [ 314 ] reported 1029 changes in gene expression of lung macrophages using IONPs while silica NPs with only 67 gene.…”
Section: Interaction Of Mnps With Biological Systemmentioning
confidence: 99%